Gene expression profiling across ontogenetic stages in the wood white (Leptidea sinapis) reveals pathways linked to butterfly diapause regulation. Issue 4 (26th February 2018) - Leal, Luis; Talla, Venkat; Källman, Thomas; Friberg, Magne; Wiklund, Christer; Dincă, Vlad; Vila, Roger; Backström, Niclas
Abstract: In temperate latitudes, many insects enter diapause (dormancy) during the cold season, a period during which developmental processes come to a standstill. The wood white ( Leptidea sinapis ) is a butterfly species distributed across western Eurasia that shows photoperiod‐induced diapause with variation in critical day‐length across populations at different latitudes. We assembled transcriptomes and estimated gene expression levels at different developmental stages in experimentally induced directly developing and diapausing cohorts of a single Swedish population of L. sinapis to investigate the regulatory mechanisms underpinning diapause initiation. Different day lengths resulted in expression changes of developmental genes and affected the rate of accumulation of signal molecules, suggesting that diapause induction might be controlled by increased activity of monoamine neurotransmitters in larvae reared under short‐day light conditions. Expression differences between light treatment groups of two monoamine regulator genes ( DDC and ST ) were observed already in instar III larvae. Once developmental pathways were irreversibly set at instar V, a handful of genes related to dopamine production were differentially expressed leading to a significant decrease in expression of global metabolic genes and increase in expression of genes related to fatty acid synthesis and sequestration. This is in line with a time‐dependent (hour‐glass) model of diapause regulation where a gradual shift in the concentration of monoamine neurotransmitters and their metabolites during development of larvae under short‐day conditions leads to increased storage of fat, decreased energy expenditures, and ultimately developmental stasis at the pupal stage.